RELATIONS OF ASHTARKHANI ABDULAZIZ KHAN WITH REPRESENTATIVES OF SCIENCE AND CULTURE - Karimjon S. Nasrilloyev (International Scientific and Current Research Conferences, 2023)
This article discusses relations of Ashtarkhani Abdulaziz Khan with representatives of science and culture.